HYGROSCOPIC, THERMAL AND CHEMICAL PROPERTIES OF CINNAMON ESSENTIAL OIL MICROPARTICLE OBTAINED BY SPRAY DRYING - Campelo, Pedro Henrique; Figueiredo, Jayne de Abreu; Ferraz, Vany; Yoshida, Maria Irene; Fernandes, Regiane Victória de Barros; Botrel, Diego Alvarenga; Borges, Soraia Vilela (Emirates Journal of Food and Agriculture, 2017)
This study aimed at evaluating the potential of gum arabic in combination with maltodextrin for the microencapsulation of cinnamon essential oil by spray drying to maximize its hygroscopic, thermal and chemical stability. The corresponding isotherm exhibited type II behavior (sigmoidal curve), and the best fit was obtained for the GAB model (E = 4.81%). Differential scanning calorimetry (DSC) analysis showed that the increased moisture content caused a significant reduction of the glass transition temperature (Tg) of the microparticles. Microparticles stored at intermediate humidity exhibited thermal stability and a lower mass loss, while storing at low temperatures led to higher antioxidant capacity and cinnamaldehyde retention.